Celebrity Spousal Interaction, Social Media, and Social Responsibility: Case Study of the Will Smith & Family - Oke, Segun (Journal of Leadership, Accountability and Ethics, 2023)
Social media has seen substantial increase in usage for family communication across the globe. Families and followers of celebrities frequently post on social media about their interactions with their spouses, family activities, and domestic disputes. Beyond fan interaction, the phenomena raise ethical concerns about broadcasting family communications for entertainment and attention, the influence of social media on celebrity spouses, and the effect of celebrity family issue information on fans. The case-study is the focus of the research’s discourse analysis, which is based on a theoretical framework for social responsibility. Findings show that celebrity spouse interactions get a lot of attention and have a big positive or negative impact on the spouses, their kids, extended family, and the fans. As a result, celebrities need to practice social responsibility in the content they provide on their platforms. Some information is delicate and might have an effect on other people’s lives and privacy. In addition to delivering simply facts or interpretative reporting on facts with clear explanations, celebrity spouses must ethically self-regulate.